Ex-Dividend Date and Stock Price Adjustment: A Systematic Literature Review of Global Market Reactions - Rinda Fithriyana; Tafdil Husni; Rida Rahim; Fajri Adrianto; Wahyu Febri Ramadhan Sudirman (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The ex-dividend date anomaly remains relevant in modern finance because, despite the predictions of the Efficient Market Hypothesis (EMH) that such arbitrage opportunities should be eliminated, empirical studies consistently show their persistence across different markets and time periods. This endurance highlights the role of real-world frictions, such as taxation differences between dividends and capital gains, transaction costs, and short-sale constraints, which prevent the complete arbitrage of price discrepancies.Purpose: This study aims to analyze the effect of the ex-dividend date on stock price adjustments using the Systematic Literature Review (SLR) approach to identify general patterns, empirical findings, and factors that influence this phenomenon.Design/methodology/approach: This study uses the SLR method by systematically reviewing relevant academic literature from various countries and time periods. The analysis is based on three main theories: Signaling Theory, Efficient Market Hypothesis (EMH), and the Clientele Effect. From an initial 101 articles retrieved (2000–2024), a rigorous screening and eligibility review resulted in 10 studies meeting the inclusion criteria, all of which examined the relationship between ex-dividend dates and stock price adjustments.Findings/Results: The results show that abnormal returns consistently occur around the ex-dividend date across different markets, indicating that price adjustments are not fully explained by dividend payouts. However, the magnitude, direction, and statistical significance of these abnormal returns are not uniform; they vary depending on market characteristics, such as the level of market development, the efficiency of trading systems, and the presence of dividend taxation rules. Company-specific conditions also play a role, with firms with higher liquidity tending to exhibit smoother price adjustments.Conclusion: The findings show that although the efficient market theory states that dividend information is directly reflected in stock prices, there are market anomalies around the ex-dividend date. This indicates that psychological factors and market structure also influence stock price dynamics.Originality/value (State of the art): This study offers originality by conducting a comprehensive global synthesis of research on ex-dividend dates and stock price adjustments, bridging insights from both classical finance theories, such as the Efficient Market Hypothesis and tax clientele effect, and behavioral perspectives that emphasize investor psychology and market frictions. Unlike earlier reviews that focused on single countries or limited periods, this study integrates evidence from diverse markets, including developed and emerging economies, and incorporates recent findings from periods of financial crises, thereby capturing how external shocks shape ex-dividend anomalies in the UK. Keywords:   abnormal return, dividend policy, efficient market, market anomalies, signaling theory